A comparison of two headless compression screws for operative treatment of scaphoid fractures - Johnson Jim (Journal of Orthopaedic Surgery and Research, 2011)
Abstract Purpose The purpose of this study was to compare the interfragmentary compression force across a simulated scaphoid fracture by two commonly used compression screw systems; the Acutrak 2 Standard and the 3.0 mm Synthes headless compression screw. Methods Sixteen (8 pairs; 6 female, 2 male) cadaver scaphoids were randomly assigned to receive either the Acutrak 2 or Synthes screw with the contralateral scaphoid designated to receive the opposite. Guide wires were inserted under fluoroscopic control. Following transverse osteotomy, the distal and proximal fragments were placed on either side of a custom load cell, to measure interfragmentary compression. Screws were placed under fluoroscopic control using the manufacturer's recommended surgical technique. Compressive forces were measured during screw insertion. Recording continued for an additional 60s in order to measure any loss of compression after installation was complete. The peak and final interfragmentary compression were recorded and paired t-tests performed. Results The mean peak compression generated by the Acutrak 2 Standard was greater than that produced by the Synthes compression screw (103.9 ± 33.2 N vs. 88.7 ± 38.6 N respectively, p = 0.13). The mean final interfragmentary compression generated by the Acutrak 2 screw (68.6 ± 36.4 N) was significantly greater (p = 0.04) than the Synthes screw (37.2 ± 26.8 N). Specimens typically reached a steady state of compression by 120-150s after final tightening. Conclusion Peak interfragmentary compression observed during screw installation was similar for both screw systems. However, the mean interfragmentary compression generated by the Acutrak 2 Standard was significantly greater. Our study demonstrates that the Synthes headless compression screw experienced a greater loss of interfragmentary compressive force from the time of installation to the final steady state compression level. The higher post-installation compression of the Acutrak 2 Standard may be attributable to the greater number of threads throughout the entire length of the screw. The clinical significance of these results, are, at this point uncertain. We do demonstrate that a fully threaded design offers a more reliable compression that may translate to more predictable bony union.